DIGITAL SPIRITUAL WELL-BEING: REORIENTASI PEMBELAJARAN PAI UNTUK MENGATASI MASALAH KESEHATAN MENTAL SISWA GENERASI Z DI SMK MA’ARIF NU KAJEN KABUPATEN PEKALONGAN - Defi Eri Winanti; Ahmad Tarifin; Dini Rahmawati; Atmim Nurona; Fita Fitriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Generation Z students in Indonesian vocational high schools (SMK) are navigating a mental health crisis fuelled by excessive social media use marked by anxiety, emotional burnout, and social isolation. These conditions are closely tied to excessive digital media consumption. This study investigates the phenomenon of digital spiritual well-being (DSW) and explores how reorienting Islamic Religious Education (PAI) can serve as a strategic educational response. DSW is defined here as the state of inner well-being formed through individuals' interactions with digital ecosystems, encompassing the capacity to harness digital content to strengthen transcendental, social, and personal dimensions within an Islamic value framework. Using a qualitative descriptive approach, data were gathered through in-depth interviews with one PAI teacher and four students, two from Grade XI and two from Grade X, at SMK Ma’arif NU Kajen, Kajen Sub-district, Pekalongan Regency, supplemented by direct classroom observation and documentation. Source and technique triangulation were applied to validate findings, analysed through Miles, Huberman, and Saldana's interactive model. Findings show that: (1) students spend 5–8 hours daily on social media, primarily TikTok and Instagram, leading to physical fatigue, digital burnout, and structural social isolation; (2) current PAI instruction, overwhelmingly lecture-based, fails to connect with students' lived digital realities; (3) students independently seek religious content online as a spiritual coping mechanism during emotional distress, a phenomenon the researchers term 'organic digital spiritual coping'; and (4) a four-pillar PAI reorientation model is proposed: practical worship reinforcement, Islamic digital ethics and media literacy, interactive technology-based learning, and repositioning the PAI teacher as a spiritual mentor. This study concludes that PAI reorientation is not a cosmetic update but a strategic imperative for responding to Generation Z's digital-era mental health crisis, contributing a novel conceptual framework of Digital Spiritual Well-Being to Islamic education discourse.